2021
DOI: 10.1128/spectrum.00029-21
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cystic Fibrosis Lung Disease Is Associated with Bacterial Community Stability

Abstract: While much research supports a polymicrobial view of the CF airway, one in which the community is seen as the pathogenic unit, only controlled experiments using model bacterial communities can unravel the mechanistic role played by different communities. This report uses a large data set to identify a small number of communities as a starting point in the development of tractable model systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…We sought to exploit available 16S rRNA gene amplicon library sequencing data and associated clinical metadata to identify a representative set of microbial communities found in persons with CF (pwCF) that we could model in vitro . A recent study from our team using k-means to cluster 16S rRNA gene amplicon sequencing relative abundance values and another machine learning approach (e.g., the gap statistic) identified five clusters as the most parsimonious number (21). This same study revealed, following the analysis of a large cross-sectional 16S rRNA gene sequence data sets and associated metadata, that the 5 community types explained 24% of variability in lung function, twice as high as any other factor or group of factors previously identified (21).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We sought to exploit available 16S rRNA gene amplicon library sequencing data and associated clinical metadata to identify a representative set of microbial communities found in persons with CF (pwCF) that we could model in vitro . A recent study from our team using k-means to cluster 16S rRNA gene amplicon sequencing relative abundance values and another machine learning approach (e.g., the gap statistic) identified five clusters as the most parsimonious number (21). This same study revealed, following the analysis of a large cross-sectional 16S rRNA gene sequence data sets and associated metadata, that the 5 community types explained 24% of variability in lung function, twice as high as any other factor or group of factors previously identified (21).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study from our team using k-means to cluster 16S rRNA gene amplicon sequencing relative abundance values and another machine learning approach (e.g., the gap statistic) identified five clusters as the most parsimonious number (21). This same study revealed, following the analysis of a large cross-sectional 16S rRNA gene sequence data sets and associated metadata, that the 5 community types explained 24% of variability in lung function, twice as high as any other factor or group of factors previously identified (21). Thus, two different approaches, using clinical outcomes data, identified five similar community types.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations